Interpretation of Biomarker Data in Diagnosis of Primary Dementias - Salardini, Arash (Seminars in Neurology, 2019)
In the last few years, an improved understanding of dementia biomarkers has significantly increased the diagnostic accuracy for dementias. The National Institutes of Health Biomarkers Definitions Working Group defines a biomarker as “a characteristic that is objectively measured and evaluated as an indicator of normal biological processes, pathogenic processes, or pharmacologic responses to a therapeutic intervention.” In the field of dementia, a biomarker is a biological measure pointing to a specific dementing pathology. Dementia biomarkers may also serve as surrogates for disease progression and as endpoints in clinical trials. Dementia biomarkers are best characterized for Alzheimer's disease, which is the most common form of primary dementia. The current “biological” conception of Alzheimer's disease is based on consideration of three biomarkers: amyloid, tau, and “neurodegeneration.” The status of these biomarkers may be determined by cerebrospinal fluid clinical chemistry or imaging. Biomarkers for other primary dementias are less reliable and rely chiefly on structural and functional imaging. When appropriate, genetic testing may help with diagnostic certainty in hereditary forms of dementia.
Keywords: dementia biomarkers; amyloid protein; tau protein; neurodegeneration; FDG-PET